Customized 3D printed helmet in the treatment of metopic craniosynostosis in a 7-month-old infant, a case report - Atallah, Huthaifa; Naeem, Rabee; Alshawabka, Amneh; Said, Anas S.; Alfatafta, Huda; Derkács, Evelin; Varga, Dorottya; Molics, Bálint (Frontiers in Pediatrics, 2025)
IntroductionMetopic craniosynostosis results in a deformed skull and hence, impacts brain growth and development. Surgery is usually applied to treat this trigonocephalic head malformation. Helmet therapy is also utilized in craniosynostosis treatment after the surgery. However, data on use of 3D printed helmets in treatment of metopic craniosynostosis is lacking. Most of the studies are published about molding helmets. Moreover, there is a lack of evidence on its clinical outcomes. Therefore, the aim of this study was to assess the use of a 3D printed helmet in treating a metopic craniosynostosis, after the endoscopy-assisted craniotomy surgical intervention.Case descriptionA 7-month-old infant who was diagnosed with metopic craniosynostosis was referred from the neurosurgeon for a custom-made 3D printed helmet, after a surgical intervention. A certified orthotist has performed further assessment, scanning, designing, and printing a customized 3D printed helmet. Thereafter, fitting and delivery were successfully completed. Patient has come for two follow-up appointments, at 2 and 5 months.ResultsFive months after the initial fitting, the head shape correction and reduction of deformity were noticed through anthropometric measures. The cranial vault asymmetrical index (CVAI) decreased from 7% to 2% and the cranial vault asymmetry (CVA) reduced from 7 mm to 3 mm.ConclusionThis case report illustrates the utilization of 3D printing technology in the treatment of metopic craniosynostosis. 3D printed helmets may offer an appropriate option for treating selective infants with metopic craniosynostosis. Thus, would introduce the 3D helmet as a following intervention for such cases after the endoscopy-assisted craniotomy surgical intervention. Further studies with a higher number of cases are compulsory to assess the effectiveness of treating metopic craniosynostosis by 3D printed helmets instead of molding helmets.